Federal Democratic Republic of Ethiopia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper reviews the evolution of inequality in Ethiopia and discusses the role of various macroeconomic policies as well as structural factors. With a Gini coefficient of 30, Ethiopia remains among the most egalitarian countries in the world. The most vulnerable households seem to experience less benefit from growth than those in the higher income deciles. In terms of tax revenue collection, Ethiopia faces the typical challenges of a developing country. It is required that Ethiopia builds on its successful experience with the Productive Safety Net Program to address the growing needs of the urban poor.